URGENSI PENGENALAN LITERASI MEDIA DIGITAL DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR - Ayu Nur Aida; Alya Azizah Putri Ariadhie; Amanda Amanda; Desty Nurmalia; Faadhilah Quratul Aini; Nasyatul Ifada; Indra Rasyid Julianto (PT. CASA CENDEKIA MEDIA, 2025)
Media literacy has become a crucial competency, particularly for elementary school students, to effectively comprehend and evaluate information from diverse sources. The integration of media literacy into Indonesian language learning at the elementary level can enhance not only students’ communication skills but also their critical and creative thinking abilities. This study highlights the significance of embedding media literacy in Indonesian language education, focusing on its implementation through platforms such as television, video, and social media. By adopting this approach, students are encouraged to develop the capacity to identify, access, and assess relevant, high quality information while making wise use of media. Employing a descriptive qualitative method with a literature review, this research explores the role of media literacy in elementary education. Findings from the literature analysis and observations at SDN Cukanggalih II reveal that media literacy enriches Indonesian language learning, fosters creativity, and deepens students’ comprehension of texts and information. Moreover, media literacy contributes to nurturing students’ character, preparing them to be intelligent, discerning, and responsible in navigating the vast and dynamic flow of information in today’s digital environment.